Descriptive Finding Regarding Factors Influencing Information Security Vulnerability: A Case Study in Electrical Company in Iran (Open International Journal of Informatics, 2016)
Implementing technology is important to enhance the enterprise information transaction but it isimpossible to secure it without organizational and human supports. Information security is aboutconfidentiality, integrity and availability of the data and due to complexity of human resources theusers have always exposed the information security to the internal threat. This paper presents adescriptive result regarding the human factors of information security vulnerability in one electricalenterprise in Iran. The result is presented based on the continuation of the previous review work. Thedescriptive analysis was performed on twenty participants’ response over qualitative investigation.Based on the descriptive scoring result, training, risk communication and emotional control are foundto be the most significant factors influencing information security vulnerability. Surprisingly securityculture and staff experience were not significantly influential in this study. In regard to future works,an in-depth thematic analysis will be performed in order to have an overall perspective regarding thefactors of concern
Keywords: Security issues; Information Security Vulnerability; Descriptive Study